Comparative Study of Jepara Carving Design in the Era of Islamic Kingdom and Colonialism Era - Irsyada, Abdulloh Eizzi (Universitas Ciputra, 2022)
Jepara carving experienced the transition of three major cultures, namely Hindu-Buddhist-Javanese to Islam and Islam to the Dutch colonial period. This research uses case studies in the form of artifacts created in each of these periods. In the Demak Kingdom era, the Bledeg Door carving design was used in the Kalinyamat Kingdom era, the Kalinyamat Mosque wall ornament carving design was used. In the Islamic Mataram Kingdom era, the Gong Senen carving was used, while in the colonial era or Kartini era, the Kartini Jewelry Box carving design was used. This research hopes to provide answers and analye whether during these cultural transitions there were significant changes to Jepara carvings, then whether these 3 major cultures had an influence on changes in Jepara carvings and what factors influenced the changes in Jepara carvings. One of the conclusions of this research is that the artifacts made during the golden age of the Islamic Kingdom of Mataram (Gong Senen) do not reflect Islamic culture at all, but instead the principles of Islamic teachings are present in the overall symbolic value of each motif. Keywords: comparative, design, Jepara carving, Islamic Kingdom, colonial